Selected Technical and Perceptual Aspects of Virtual Reality Displays - Riecke, B. E; Nusseck, H. G; Schulte-Pelkum, J. (Technical report, Max Planck Institute for Biological Cybernetics, 2006)
There is an increasing amount of different presentation techniques available for producing visual Virtual Reality (VR) scenes. The purpose of this chapter is to give a brief and introductory overview of existing VR presentation techniques and to highlight advantages and disadvantages of each technique, depending on the specific applications. This should enable the reader to design and/or improve their VR visualization setup in terms of both the perceptual aspects and the effectiveness for a given task or goal . In this overview, we relate the different types of presentation techniques to aspects of human physiology of visual perception which have important implications for VR setups. This will, by no means, be a complete overview of all physiological aspects. For a detailed overview and introduction, see, e.g., Goldstein (2002). The aim of a visual simulation is to achieve a convincing and perceptually realistic presentation of the simulated environment. Ideally, the user should feel present in the virtual environment and not be able to tell whether it is real or simulated. The human visual system uses several cues to form a percept of the surrounding environment. We will have a closer look at some of these cues in the first section, as they are of crucial importance when looking at simulated scenes. The remaining sections are concerned with possible technical implementations and how these relate to the perceptual aspects and effectiveness for a given task.
Keywords: MPI-TR; Riecke; Riecke_2006; TR; bernhard-riecke; iSpaceWeb